Isolation, purification, structural characteristic and antioxidative property of polysaccharides from A. cepa L. var. agrogatum Don - Hongcheng Liu; Hongxiu Fan; Jing Zhang; Shanshan Zhang; Wenting Zhao; Tingting Liu; Dawei Wang (Food Science and Human Wellness)
Allium cepa L. var. agrogatum Don (ALAP) is commonly consumed in China as well as other regions and has various beneficial health effects. A novel acidic polysaccharide (named ALAP-21) was obtained from ALAP by ultrasonic and microwave-assisted extraction and purification using DEAE-52 anion exchange and Sephadex G-100 columns. The monosaccharide composition, structural and antioxidative properties of ALAP-21 were investigated by GC–MS chromatography, FT-IR and NMR spectroscopies and three antioxidative activity tests in vitro. The results showed that ALAP-21 was a heteropolysaccharide composed of glucose, galacturonic acid, mannose, galactose, arabinose, rhamnose, xylose, fructose and glucuronic acid with a relative molar ratio of 26.282: 27.546: 11.400: 4.781: 2.467: 2.445: 3.622: 1.106: 1.753, owning (1→4)-α-d-Glcp, (1→4)-α-d-GalAp6Me3OA, (1→4)-β-d-Galp6OMe, (1→2)-α-l-Rhap, (1→4)-β-d-Manp glycosidic linkages. (1→4)-α-d-Glcp and (1→4)-α-d-GalAp6Me3OA residues might be the main components of the sugar chain backbone of ALAP-21. Furthermore, ALAP-21 exhibited high potential for DPPH radicals (82.02%), hydroxyl radicals (53.33%) and superoxide anion radicals (50.28%). These results provide a reference for further research and rational development of ALAP polysaccharides. Keywords: Polysaccharides, Allium cepa L. var. agrogatum Don, Structural characterization, Antioxidative property